Maternal and child health inequalities among migrants: the case of Haiti and the Dominican Republic - Roberta Bouilly; Giovanna Gatica-Domínguez; Marilia Mesenburg; Francisco I. Cáceres Ureña; Daniel G. P. Leventhal; Aluísio J. D. Barros; Cesar G. Victora; Fernando C. Wehrmeister (Pan American Health Organization, 2020)
Objective. To assess coverage and inequalities in maternal and child health interventions among Haitians, Haitian migrants in the Dominican Republic and Dominicans. Methods. Cross-sectional study using data from nationally representative surveys carried out in Haiti in 2012 and in the Dominican Republic in 2014. Nine indicators were compared: demand for family planning satisfied with modern methods, antenatal care, delivery care (skilled birth attendance), child vaccination (BCG, measles and DPT3), child case management (oral rehydration salts for diarrhea and careseeking for suspected pneumonia), and the composite coverage index. Wealth was measured through an asset-based index, divided into tertiles, and place of residence (urban or rural) was established according to the country definition. Results. Haitians showed the lowest coverage for demand for family planning satisfied with modern methods (44.2%), antenatal care (65.3%), skilled birth attendance (39.5%) and careseeking for suspected pneumonia (37.9%), and the highest for oral rehydration salts for diarrhea (52.9%), whereas Haitian migrants had the lowest coverage in DPT3 (44.1%) and oral rehydration salts for diarrhea (38%) and the highest in careseeking for suspected pneumonia (80.7%). Dominicans presented the highest coverage for most indicators, except oral rehydration salts for diarrhea and careseeking for suspected pneumonia. The composite coverage index was 79.2% for Dominicans, 69.0% for Haitian migrants, and 52.6% for Haitians. Socioeconomic inequalities generally had pro-rich and pro-urban pattern in all analyzed groups. Conclusion. Haitian migrants presented higher coverage than Haitians, but lower than Dominicans. Both countries should plan actions and policies to increase coverage and address inequalities of maternal health interventions.